2003
DOI: 10.1046/j.1529-8019.2003.01622.x
|View full text |Cite
|
Sign up to set email alerts
|

Balneotherapy in dermatology

Abstract: Balneotherapy and spa therapy emerged as an important treatment modality in the 1800s, first in Europe and then in the United States. Balneotherapy involves immersion of the patient in mineral water baths or pools. Today, water therapy is being practiced in many countries. Examples of unique and special places for balneotherapy are the Dead Sea in Israel, the Kangal hot spring in Turkey, and the Blue Lagoon in Iceland. Bathing in water with a high salt concentration is safe, effective, and pleasant for healing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
173
0
21

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(194 citation statements)
references
References 43 publications
0
173
0
21
Order By: Relevance
“…Sulfurs are able to penetrate the skin, and a sulfur-rich balneotherapy is known to be effective in the treatment of psoriasis. 22 This is the reason why we used NaHS at concentrations that are higher than those of endogenously produced HS À , but comparable to those found in most natural sources of sulfurs. According to earlier studies, keratinocytes of hyperplastic epidermis express high levels of pERK with the classical nuclear localization, whereas keratinocytes of normal skin show low pERKs levels with a main cytoplasmic localization.…”
Section: H2s Downregulates Erk In Keratinocytesmentioning
confidence: 97%
See 1 more Smart Citation
“…Sulfurs are able to penetrate the skin, and a sulfur-rich balneotherapy is known to be effective in the treatment of psoriasis. 22 This is the reason why we used NaHS at concentrations that are higher than those of endogenously produced HS À , but comparable to those found in most natural sources of sulfurs. According to earlier studies, keratinocytes of hyperplastic epidermis express high levels of pERK with the classical nuclear localization, whereas keratinocytes of normal skin show low pERKs levels with a main cytoplasmic localization.…”
Section: H2s Downregulates Erk In Keratinocytesmentioning
confidence: 97%
“…15 However, the effects promoted by exogenous H 2 S on keratinocytes and/or skin-derived blasts have been poorly investigated. The specific interest derives from the potential applications of the results, as sulfur is able to penetrate the skin and a sulfur-rich balneotherapy, known to be effective in the treatment of psoriasis, 22 might turn useful also in other T-cell-mediated autoimmune diseases of the skin.…”
mentioning
confidence: 99%
“…Balneotherapy and spa therapy emerged as important European treatment modalities during the 1800s (Matz et al 2003) that are still practiced in many countries today. Carbon dioxide (CO 2 ) balneotherapy using hot springs containing free CO 2 at concentrations above 1 g·L -1 (ppm) (CO 2 -hot spring) has long been clinically applied to improve cardiovascular symptoms (Savin et al 1995;Toriyama et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…25 According to previous studies, keratinocytes of hyperplastic epidermis express high levels of pERK and IL-8. pERKs show the classical nuclear localization, while keratinocytes of normal skin show low pERKs levels with a main cytoplasmic localization.…”
Section: Resultsmentioning
confidence: 92%
“…21,22 Many studies have been published on the involvement of hydrogen sulfide in inflammation, and evidence has been shown for both pro-or anti-inflammatory roles of H 2 S. 23,24 Recently, we have demonstrated that hydrogen sulfide can impair human keratinocytes adhesion and proliferation by impairing the activation of Raf-MEK-ERK pathway. 22 The specific interest to hydrogen sulfide derives from the potential applications of the results, as sulfur is able to penetrate the skin and a sulfur-rich balneotherapy, known to be effective in the treatment of psoriasis, 25 might turn useful in this disease. In this context, we have also demonstrated that H 2 S can exert a subset-specific toxicity on peripheral blood lymphocytes, which die by a caspase-independent mechanism of necrosis after a rapid loss of mitochondrial membrane potential, and not by apoptosis.…”
mentioning
confidence: 99%